Heating systems of detached houses in Finland : a review to house owners’ plans, attitudes and values - Julkunen, Nina (2024)
Most of temperature rising greenhouse gas emissions are originated from energy and an important part of tackling climate change is a transition from fossil energy sources to renewable energy. Beside European Union, Finland has ambitious targets to decrease the GHG-emissions and improving buildings energy efficiency has important role in reaching the goals. There are more than one million residential detached or semi-detached houses in Finland, and small house living has been traditionally very popular mode of living in Finland. Due to long and cold winters, the heating of buildings is consuming a large share of a buildings’ total energy demand. Heating of houses have also become more an economical issue due to increased energy costs. Historically high electricity prices hit the market in the late 2022’s, causing an unexperienced energy crisis in Finland. The aim of the study was to investigate house owners plans to change or update their heating system, to find out does the heating system effect on house value from house owner’s perspective, to examine attitudes towards tightening energy efficiency requirements and the statutory energy performance certificate EPC, that provides information about the energy efficiency of the house, and to find out how much the environmental friendliness of the heating system weights in relation to the costs. Quantitative research was carried out by using a web-based questionnaire to collect the data. The results of the study showed that a significant part of house owners did consider changing or updating the heating system of their house to more energy efficient system. For the most house owners, the costs were the most important driver and the environmental aspects played less important role. Even there were many negative tones towards EPC amongst the house owners, it was widely agreed that the type of heating system does have strong effect on house value. As a conclusion, speeding up the change to update the heating systems to more energy efficient and environmentally friendly systems, it could be emphasized more as a value adding long-term investment, instead of a plain direct cost, to activate the house owners to change or update the heating systems of their houses.